Correlation between zinc intake and hair zinc levels to morbidity of infectious diseases in children aged 24-35 months in Jakarta - Dyah Arum Kusumaningtyas; Diana Sunardi; Rini Sekartini (World Nutrition Journal, 2022)
According to WHO, preventable diseases, including infectious diseases, are the most common cause of death in children. Based on Indonesia's 2019 health profile data, the top five morbidity and mortality in children aged 1-4 years are acute respiratory tract infections (ARI) of (25.8%), pneumonia (21.7%), fever (14%), diarrhea and gastrointestinal disease (14.4%). Zinc has an important role in immunity especially for younger child